Everyday karma - Harra, Carmen (London, United Kingdom : Piatkus, 2002)
A thoughtful exploration of karma and how it can be used in a positive way to heal wounds and resolve problems.
Part 1. Entering the invisible world: The land of spirit and light -- Part 2. Living in the visible world: A web of infinite possibilities -- Part 3. Healing your karma: The world of everyday action.
Keywords: KARMA